2016
DOI: 10.1159/000444367
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Analysis of <b><i>Klebsiella pneumoniae </i></b>Causing Liver Abscess in China

Abstract: Objective: Hypervirulent Klebsiella pneumoniae (hvKP) has been characterized as the major pathogen associated with the development of liver abscesses. Although the prevalence of K. pneumoniae in liver abscesses in Chinese patients is on the rise, methods for the early laboratory identification and recognition of hvKP are lacking, and hvKP detection and surveillance are thus limited. Methods: A retrospective study was conducted in 240 patients with cultures that were positive for K. pneumoniae, who were hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
(31 reference statements)
2
12
1
Order By: Relevance
“…, we found that the main capsular serotype of hvKp in this hospital is K2 (17, 28.81%), K57 (15, 25.42%) and K1 (14, 23.73%), and the rate of K57 type was even slightly higher than that of the K1 type. K57 has also been reported in other reports with different detection rates, such as 9.6% (8/84)[25], 13.6% (3/22) [17], 10.4% (10/96) [26] and 18.9% (7/37)[27], suggesting that the serotype distribution of hvKp varied in different regions. The 59 strains of hvKp were also subjected to PFGE molecular typing analysis, and the results suggested that the same serotype strains can almost be classified into the same cluster, but the same cluster can be divided into different band types according to different genetic backgrounds, indicating that PFGE molecular typing technology can further differentiate various strains based on genetic characters.…”
supporting
confidence: 74%
“…, we found that the main capsular serotype of hvKp in this hospital is K2 (17, 28.81%), K57 (15, 25.42%) and K1 (14, 23.73%), and the rate of K57 type was even slightly higher than that of the K1 type. K57 has also been reported in other reports with different detection rates, such as 9.6% (8/84)[25], 13.6% (3/22) [17], 10.4% (10/96) [26] and 18.9% (7/37)[27], suggesting that the serotype distribution of hvKp varied in different regions. The 59 strains of hvKp were also subjected to PFGE molecular typing analysis, and the results suggested that the same serotype strains can almost be classified into the same cluster, but the same cluster can be divided into different band types according to different genetic backgrounds, indicating that PFGE molecular typing technology can further differentiate various strains based on genetic characters.…”
supporting
confidence: 74%
“…Whole-genome sequencing of 30 hvKP isolates from different geographic origins revealed that all hvKP were rmpA positive (Struve et al, 2015 ). Several studies from China also showed that 92–100% of hvKP isolates were positive for rmpA (Liu et al, 2014 ; Sun et al, 2016 ; Wu et al, 2017 ). Regardless of the investigated infection site, most hvKP isolates appear to have the rmpA gene (Ku et al, 2008 ; Yu et al, 2008 ; Lee et al, 2010 ; Decré et al, 2011 ; Qu et al, 2015 ; Guo et al, 2016 ; Zhang et al, 2016 ; Wu et al, 2017 ; Zhan et al, 2017 ).…”
Section: Factors Associated With Hypervirulence Of Hvkpmentioning
confidence: 97%
“…Many reports showed that an iucABCD - iutA gene was more common in hvKP strains than in cKP strains (Table 1 and Table S1 ). In China, many studies have reported the high prevalence (69–96%) of aerobactin in hvKP isolates (Guo et al, 2016 , 2017 ; Sun et al, 2016 ; Yan et al, 2016 ; Ye et al, 2016 ; Zhang et al, 2016 ; Zhao et al, 2016 ; Wu et al, 2017 ; Zhan et al, 2017 ). A study in Taiwan also showed that the prevalence of aerobactin was 100% in capsular K1 and K2 isolates and 86% in non-K1/K2 isolates.…”
Section: Factors Associated With Hypervirulence Of Hvkpmentioning
confidence: 99%
“…Alarmingly, increasing studies reported that multi-drug-resistant, even carbapenem-resistant hvKP isolates have been emerged (Yang et al, 2014 ; Yao et al, 2015 ; Zhang et al, 2015 ), which is becoming an important threat to public health. Recently, many studies from China described the prevalence, clinical presentations and epidemiology of hvKP isolates (Liu et al, 2014 ; Yang et al, 2014 ; Qu et al, 2015 ; Yao et al, 2015 ; Sun et al, 2016 ; Zhao et al, 2016 ). However, the limitations of these studies included limited number of K. pnuemoniae involved, short span of investigation and focusing a specific infection.…”
Section: Introductionmentioning
confidence: 99%